Problematika Hukum Terhadap Pembebasan (Asimilasi) Narapidana di Tengah Covid-19 (Studi Kasus Bapas II Watampone) - Ikbal, Ikbal; Safriani, Andi (Alauddin Law Development Journal, 2022)
Liberation of prisoners with a new news assimilation system in Indonesia's criminal system. The word or term assimilation has been stipulated in law number 12 of 1995 concerning correctional services and is increasingly popular in public after the issuance of Permenkumham HAM number 10 of 2020 which provides freedom for prisoners with certain keywords. From the results of research, especially in the Class II Watampone Correctional Center as the person in charge of supervising and guiding released prisoners. The author finds that there are still many problems (problems) faced by the Watampone Class II Correctional Center in carrying out this assimilation program.